2016
DOI: 10.1093/plankt/fbv117
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of Eucalanoid copepods within the Costa Rica Dome area of the Eastern Tropical Pacific

Abstract: A variety of ecological strategies for tolerance of low-oxygen conditions within the Costa Rica Dome (CRD) area of the Eastern Tropical Pacific are documented for the copepod family Eucalanidae. During the summer of 2010, we compared the ecological strategies used by the Eucalanidae inside and outside the central CRD region. We compared the vertical and horizontal distributions of five species, ,, , and together with species, in the epipelagic (upper 200 m) among four locations, which we grouped into a section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Chen (1986) analyzed vertical distributions for both individual copepod taxa and large multispecies samples, collected with openingclosing bongo nets, at stations along a transect from Baja California to the Equator during the Krill Expedition. Copepod vertical distributions in the Costa Rica Dome, long known as a productive feature important to fisheries (Fiedler, 2002;Landry et al, 2016), have been reported (Décima et al, 2016;Fiedler, 2002;Jackson and Smith, 2016;Landry et al, 2016;Sameoto, 1986;Vinogradov et al, 1991;Wishner et al, 2013). Copepod vertical distributions from MOC-NESS tows near the Volcano 7 seamount in the ETNP (13 • N, 102 • W) were described by Saltzman and Wishner (1997).…”
Section: Overviewmentioning
confidence: 98%
“…Chen (1986) analyzed vertical distributions for both individual copepod taxa and large multispecies samples, collected with openingclosing bongo nets, at stations along a transect from Baja California to the Equator during the Krill Expedition. Copepod vertical distributions in the Costa Rica Dome, long known as a productive feature important to fisheries (Fiedler, 2002;Landry et al, 2016), have been reported (Décima et al, 2016;Fiedler, 2002;Jackson and Smith, 2016;Landry et al, 2016;Sameoto, 1986;Vinogradov et al, 1991;Wishner et al, 2013). Copepod vertical distributions from MOC-NESS tows near the Volcano 7 seamount in the ETNP (13 • N, 102 • W) were described by Saltzman and Wishner (1997).…”
Section: Overviewmentioning
confidence: 98%
“…Overall population distributions at particular locations in this and prior work usually encompassed a range of oxygen concentrations, although most earlier studies had relatively broad sampling strata that did not isolate specific oxygen ranges or did not have electronic oxygen sensors co-located on the zooplankton sampling systems. DVM by this species, usually over a relatively short depth range between the near-surface and UO, was reported by some authors at some times and places, but not others (Escribano et al, 2009;Jackson and Smith, 2016).…”
Section: Diapausing In the Omzmentioning
confidence: 54%
“…Chen (1986) analyzed vertical distributions for both individual copepod taxa and large multispecies samples, collected with opening-closing bongo nets, at stations along a transect from Baja California to the equator during the Krill Expedition. Copepod vertical distributions in the Costa Rica Dome, long known as a productive feature important to fisheries (Fiedler, 2002;Landry et al, 2016), have been reported (Décima et al, 2016;Fiedler, 2002;Jackson and Smith, 2016;Landry et al, 2016;Sameoto, 1986;Vinogradov et al, 1991;Wishner et al, 2013). Copepod vertical distributions from MOCNESS tows near the Volcano 7 seamount in the ETNP (13°N 102°W) were described by Saltzman and Wishner (1997).…”
Section: Epipelagic Habitat Compression and Mixed Layer Species Respomentioning
confidence: 98%
See 1 more Smart Citation
“…In TrE, as found in our study, the wide ranges in the physico-chemical variables in upper 1000 m demand a high tolerance for the organisms to have an active migration tendency. Though the major driving force for the DVM may differ from species to species, as found in several earlier studies [31,32], in TrE, the major challenging factor for organisms is to be tolerant to this wide range of the physico-chemical variables. This, in turn, results in restricted vertical migration of the organism present in the system.…”
Section: Discussionmentioning
confidence: 90%